2023
DOI: 10.3390/cells12131711
|View full text |Cite
|
Sign up to set email alerts
|

Activation Ratio Correlates with IQ in Female Carriers of the FMR1 Premutation

Abstract: Carriers of the FMR1 premutation (PM) allele are at risk of one or more clinical conditions referred to as FX premutation-associated conditions (FXPAC). Since the FMR1 gene is on the X chromosome, the activation ratio (AR) may impact the risk, age of onset, progression, and severity of these conditions. The aim of this study was to evaluate the reliability of AR measured using different approaches and to investigate potential correlations with clinical outcomes. Molecular and clinical assessments were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Additionally, several studies have suggested that lower AR values could be linked to cognitive and behavioral challenges in female PM carriers [ 97 , 106 , 107 , 108 , 109 , 110 ], potentially affecting the risk, severity, and age of onset of FXPAC. Despite numerous studies investigating the role and impact of the AR in PM carriers, there are discrepancies among their findings that may be partially attributable to technical variability, as previously reported [ 86 , 111 , 112 , 113 , 114 ], or to differences in the methods employed to calculate the AR (as discussed in Protic et al, this special issue [ 115 ]). At the International Premutation Conference, novel data were presented demonstrating a noteworthy correlation between clinical measures and the AR.…”
Section: The Molecular Basis Of Fxpacmentioning
confidence: 99%
“…Additionally, several studies have suggested that lower AR values could be linked to cognitive and behavioral challenges in female PM carriers [ 97 , 106 , 107 , 108 , 109 , 110 ], potentially affecting the risk, severity, and age of onset of FXPAC. Despite numerous studies investigating the role and impact of the AR in PM carriers, there are discrepancies among their findings that may be partially attributable to technical variability, as previously reported [ 86 , 111 , 112 , 113 , 114 ], or to differences in the methods employed to calculate the AR (as discussed in Protic et al, this special issue [ 115 ]). At the International Premutation Conference, novel data were presented demonstrating a noteworthy correlation between clinical measures and the AR.…”
Section: The Molecular Basis Of Fxpacmentioning
confidence: 99%